A style analysis of the following works: Fear of the Hunted by Dustin Lowes, Three Preludes for Solo Marimba by Ney Rosauro, buttonwood by Evan Chapman, Etude 29 from Trente Études pour Timbales by Jacques Delécluse, Canción de los Árboles by Kurt Gartner, and Mudra by Bob Becker - Johnson, Jack Andrew (Kansas State University, 2023)
This report offers a comprehensive analysis of the pieces performed during my master's recital on March 5, 2023, at Kirmser Hall on the campus of Kansas State University. It is intended to assist musicians planning to perform and scholars seeking to gain a deeper understanding of the compositions included in the recital. Each piece has been analyzed using Jan Larue's style analysis method, except for harmonic and melodic analysis for some compositions.
Keywords: Music; Percussion; Analysis